Therapeutic strategies for gastric cancer targeting immune cells: Future directions - Zhao, Yan; Bai, Yuansong; Shen, Meili; Li, Yapeng (Frontiers in Immunology, 2022)
Gastric cancer (GC) is a malignancy with a high incidence and mortality, the emergence of immunotherapy has brought survival benefits to gastric cancer patients. Compared with traditional therapy, the immunotherapy has the advantages of durable response, long-term survival benefit, lower toxicity. Therefore, targeted immune cells is the most promising therapeutic strategy in the field of oncology. In this review, we introduce the role and significance of each immune cell in the tumor microenvironment of gastric cancer and summarize the current landscape of immunotherapy in gastric cancer, which including immune checkpoint inhibitors, adoptive cell therapy (ACT), dendritic cells (DC) vaccines, reduction of M2 tumor-associated macrophage (TAM), N2 tumor-associated neutrophil (TAN), Myeloid-derived suppressor cell (MDSC), regulatory T cells (Tregs), regulatory B cells (Breg) in the tumor microenvironment and reprogram TAM and TAN into tumor killer cells. The most widely used immunotherapy strategies are the immune checkpoint inhibitor programmed cell death 1/programmed death-ligand 1 (PD-1/PD-L1) antibody and CTLA-4 (cytotoxic T lymphocyte–associated protein 4) antibody and chimeric antigen receptor T (CAR-T) in ACT and these therapeutic strategies have significant antitumor efficacy in solid tumors and hematological tumors. targeting other immune cells provide a new direction for the immunotherapy of gastric cancer despite the clinical data are relatively weak, but which have been confirmed to restore or enhance anti-tumor immune function in preclinical studies and some treatment strategies have entered the clinical trial stage. and it is expected that more and more effective immune cell-based therapeutic methods will be developed and applied.